The Effectiveness of the Spiritual Emotional Freedom Technique (SEFT) to Reduce Anxiety in Hypertensive Patients in Hospital X Banyuwangi City in Terms of Big Five Personality Traits - Ajeng Pradnyaswari Suryawirawan; Noviekayati, IGAA; Santi, Dyan Evita (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to examine the effectiveness of the Spiritual Emotional Freedom Technique therapy to reduce anxiety in patients with hypertension and to determine whether there are differences in anxiety reduction based on the five dimensions of the Big Five personality. This study consisted of 6 subjects who met the research criteria after going through a screening process involving medical records, measuring anxiety using HARS, and assessing personality dimensions using the Big Five scale. SEFT (Spiritual Emotional Freedom Technique) therapy was given as an intervention to reduce anxiety in patients. Data analysis was performed using the Wilcoxon Signed Ranks Test to compare anxiety before and after the intervention. In addition, the Kruskal-Wallis Test was used to test the difference in anxiety between different personality groups. The results of the analysis showed that SEFT (Spiritual Emotional Freedom Technique) therapy was effective in reducing the anxiety of hypertensive patients. The Wilcoxon test showed a significant decrease in anxiety levels, with an average value of patient anxiety before intervention of 33.50 and after intervention of 23.00. This proves that SEFT therapy can reduce anxiety in patients. Meanwhile, the Kruskal Wallis Test showed no significant difference in anxiety reduction based on personality with a p-value (Asymp.Sig) of 0.303 > 0.05. Thus, it can be concluded that although SEFT therapy can reduce anxiety in hypertensive patients, personality does not affect the response to this intervention